2012
DOI: 10.1016/j.jts.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathies et plasma riche en plaquettes (PRP) : applications cliniques. Revue de la littérature

Abstract: Certaines lésions tendineuses chroniques apparaissent régulièrement résistantes aux traitements conservateurs. Cette revue actualise le traitement des lésions tendineuses par plasma riche en plaquettes (PRP). Etant donné le caractère récent de ce traitement dans le domaine médico-sportif, les études cliniques réalisées à ce jour n'ont pas confirmé les effets bénéfiques obtenus in vitro. Certaines études démontrent une amélioration de la symptomatologie suite au traitement par PRP, mais d'autres études apparais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…), others remain chronic. It is for this reason that a lot of research has been carried out to develop or adapt treatments for such rebel conditions, among which PRP and HA (13,28). Some clinical studies have previously evaluated the effect of PRP in the treatment of proximal patellar tendinopathies (6,23,24,29).…”
Section: Discussionmentioning
confidence: 99%
“…), others remain chronic. It is for this reason that a lot of research has been carried out to develop or adapt treatments for such rebel conditions, among which PRP and HA (13,28). Some clinical studies have previously evaluated the effect of PRP in the treatment of proximal patellar tendinopathies (6,23,24,29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the patellar tendon appear to be more positive than other tendons. However, as already observed in previous reviews on PRP [5][6][7][8][9][10][11][12][13][14][15] , the more recent studies cannot conclude that PRP is really efficient in the treatment of tendinopathy, even if most of the low level studies remain very encouraging. Moreover, many of the authors of the articles reporting success of PRP application (essentially with leukocytes rich PRP) have conflicts of interest.…”
Section: Discussionmentioning
confidence: 92%
“…In a certain number of cases, the aim is also to reduce the duration of functional impotence and to encourage an early return to physical activity. However, currently the use of these PRPs remains a topic of debate and even controversy [7][8][9][10][11][12][13][14][15] . Table 1 presents the clinical studies discussed in this review.…”
Section: B Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that PRP injection improves the healing process of acute tendon lesions in a rat model, 2,16,28 especially in the early phase of healing, 15 even though the efficacy of this treatment applied to human subjects is still debated. 3,5,6,13 Moreover, a 5-week eccentric training protocol performed on healthy rat tendons significantly increased the force and energy required to tear the tendon in a simple tensile test. 17 In human subjects undergoing physical therapy after a tendon injury, eccentric training is a key factor for a successful recovery, 1,7,8 if we assume that the latter is related to the biomechanical properties of the tendon.…”
Section: Discussionmentioning
confidence: 98%